HUBUNGAN SIKAP DAN PEKERJAAN DENGAN KUNJUNGAN NIFAS DI WILAYAH KERJA PUSKESMAS TOLAMAERA KECAMATAN GUNUNG SITOLI IDANOI - Sianipar, Yesica Geovany; Farasi, Elina; Magdalena br Barus (Midwifery And Complementary Care, 2025)
Background: Postpartum visits are visits made by postpartum mothers to health workers during the postpartum period, which starts after the birth of the placenta and ends when the uterine devices return to their pre-pregnancy state.The postpartum period lasts for approximately 6 weeks. Postpartum visits are highly recommended for postpartum mothers to find out their health conditions. Postpartum visits conducted by postpartum mothers at Tolamaera Health Center, Gunungsitoli Idanoi Distric North Sumatera Province were not complied with which caused many complaints. Objective:. to determine the relationship between attitude, education, and work with postpartum visits at Tolamaera Health Center, Gunungsitoli Idanoi Distric North Sumatera Province. Methods: This research is analytic study using a cross sectional design, a sample of 41 people taken by total sampling. Analysis was carried out univariately and bivariately with the chisquare test with a p-value <0.05. Result: The results of this study indicate that the variables associated with postpartum visits are attitude (p value = 0.048) and occupation (p value = 0.009). Conclusion: There is a relationship between work and maternal attitudes towards postpartum visits in the Tolamaera Health Center Working Area, Gunungsitoli Idanoi District, Gunungsitoli City, North Sumatra Province. Keywords: Attitude, Occupation, Postpartum Visit